Analisis Inovasi Produk terhadap Kinerja Restoran melalui Pemanfaatan Teknologi sebagi Variabel Mediasi (Studi Kasus pada Restoran di Kota Sukabumi) - Nida Hopia; R. Deni Muhammad Danial; Asep Muhamad Ramdan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid growth of the restaurant industry in Sukabumi City has intensified competition, requiring restaurant owners to continuously improve their performance. However, many restaurants still face challenges in optimizing technology to support product innovation and operational effectiveness. This study aims to examine the effect of product innovation on restaurant performance, with technology utilization as a mediating variable. A quantitative research approach was employed using a survey method. Data were collected through questionnaires distributed to 158 restaurant owners operating in Sukabumi City. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3 software. The results show that product innovation has a positive and significant effect on both technology utilization and restaurant performance. Furthermore, technology utilization significantly influences restaurant performance and plays an important mediating role in strengthening the relationship between product innovation and restaurant performance. These findings indicate that product innovation becomes more effective in improving restaurant performance when supported by optimal technology utilization. This study highlights the importance of integrating product innovation and technology adoption as a strategic approach to enhance operational performance and competitiveness in the restaurant industry.